Asset Purchase Programs in European Emerging Markets - Arena, Marco; Bems, Rudolfs; Ilahi, Nadeem; Lee, Jaewoo (Washington, D.C. : International Monetary Fund, 2021)
Several emerging market central banks in Europe deployed asset purchase programs (APPs) amid the 2020 pandemic. The common main goals were to address market dysfunction and impaired monetary transmission, distinct from the quantitative easing conducted by major advanced economy central banks. Likely reflecting the global nature of the crisis, these APPs defied the traditional emerging market concern of destabilizing the exchange rate or inflation expectations and instead alleviated markets successfully. We uncover some evidence that APPs in European emerging markets stabilized government bond markets and boosted equity prices, with no indication of exchange rate pressure. Examining global and domestic factors that could limit the usability of APPs, in the event of renewed market dysfunction we see a potential scope for scaling up APPs in most European emerging markets that used APPs during the pandemic, provided that they remain consistent with the primary objective of monetary policy and keep a safe distance from the risk of fiscal dominance. As central banks in the region move towards monetary policy tightening, the tapering, ending, and unwinding of APPs must also be carefully considered. Clear and transparent communication is critical at each step of the process, from the inception to the closure of APPs, particularly when a large shock hits and triggers a major policy shift.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Corporate Finance and Governance; Economic Development; Emerging Markets; Monetary Policy; Saving and Capital Investment